Monitoring The Financial Policy Application in The School Fund Allocation - Istaryatinigtias Istaryatinigtias; Rismita Rismita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study explains the monitoring of financial management policies in allocating The School Operational Assistance funds regarding compliance with established regulations. The problem in this study is that the Education Operational Costs (BOP) have not allocated financing for Industrial Work Practice (Prakerin) activities of Vocational High School students / students. A qualitative research method with the evaluation approach of Stake's Countenance. The subject of research is an evaluation instrument for the school quality improvement program based on the basic education data system Data collection is interview, documentation, observation. The data analysis technique describes each stage of the evaluation. The implementation of financial policies in allocating school funds is in accordance with the monitoring criteria and the economic theory of education regarding human capital that focuses on economic knowledge and values and actions. The contribution of vocational high school human capital is centered on students' values and actions. The results of this study will contribute to schools, the provincial education office and the district education office, to implement financial policies used to manage school finances effectively and efficiently based on the allocation of funds that have been determined in the Financial Policy technical guidelines.